Café Society
XI, 208 p.
Keywords: While tracing the historical emergence of the café as a social institution and noting its multiple faces and functions in the modernity of the occident, three themes run like threads of varying texture through the chapters: the social connectivity and inclusion of cafés, café as surrogate office, and café as site of exchange for news and views.